Nuclear power, democracy, development, and nuclear warheads: Determinants for introducing nuclear power - Lars Sorge; Anne Neumann; Christian R. von Hirschhausen; Ben Wealer (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper analyzes the nature of democratic development in a nation on the process of introducing nuclear power over the period 1960 - 2017 for an unbalanced panel of 171 countries. Given the involved political process of introducing nuclear power and its political importance, as well as the current tendency of about 30 countries to "go nuclear", this question is both of historic and current interest. We apply a multinomial logistic regression approach that relates the likelihood of a country to introduce nuclear power to its level of democratic quality and nuclear warhead possession. The model results suggest that countries with lower levels of democratic development are more likely to introduce nuclear power. Our results moreover indicate that countries which possess at least one nuclear warhead are more likely to continue to use nuclear power instead of not using nuclear power at all. We discuss these results in the context of the public policy debate on nuclear power, yet beyond energy and environmental issues addressing international relations, conflict, and security issues connected to nuclear energy.
Keywords: P48; Q34; Q01; C35; 330; nuclear power; nuclear warhead; democracy; multinomial logit; panel data